Size Distribution, Length-Weight Relationship, and Catch per Unit Effort of Frigate Tuna, Auxis thazard (Lacepède, 1800) in Tawi-Tawi Waters, Southern Philippines, Caught Using Multiple Handline - AJIK, Jaro; TAHİLUDDİN, Albaris (Marine Science and Technology Bulletin, 2021)
Frigate tuna Auxis thazard (Lacepède, 1800) is the most dominant species caught by the multiple handline in the coastal and offshore fishing grounds of Tawi-Tawi, southern Philippines. In this study, we investigated the size distribution, length-weight relationship, and catch per unit effort of frigate tuna (A. thazard) in Tawi-Tawi waters, southern Philippines, caught using multiple handline. A total of 383 frigate tuna fish were sampled with a size distribution (total length) ranging from 16.5 to 34 cm. The length-weight relationship of frigate tuna was W=8×10-3×TL3.139, where the b value of 3.139 indicates a positive allometric growth pattern. The catch per unit effort of the used gear was 2.49±0.52 kg/hr.
Keywords: Balıkçılık Yönetimi; Fisheries Management; Auxis thazard; frigate tuna; catch per unit effort; length-weight relationship; Philippines; 14. Life underwater